Atuação de intérpretes de língua de sinais na pósgraduação lato sensu: estratégias adotadas no processo dialógico - Santiago, Vânia de Aquino Albres (2013)
The challenge of the inclusion of people with disabilities in different segments of social relations is not new and it is undoubtedly a complex process. In formal education deaf students are also offered an interpretation service performed by a Translator/ Interpreter of Brazilian Sign Language, in this dissertation referred to as educational interpreter (EI). Thus, under the assumptions of enunciative-discursive perspective, the objective of this study is to identify (1) strategies adopted in the interpretation from Portuguese to Brazilian Sign Language in the context of a Lato sensu graduate course and (2) influences experienced by an interpreter in this activity. The methodology adopted was participant ethnographic research, since it enables forms of interaction between the researcher and the subjects that no other technique does. In this study Libras interpreters (the author and other professional researcher invited) participated, in addition, an adult deaf student, a professor and other hearing students took part. Data collection was conducted through video recording of the interpretation of the classes in the university s classroom. The classes analyzed (part of a specialization course on "Sustainability - in the context of construction / architecture) had as subject "Energy Efficiency." The activity of educational interpreting, especially in higher education is a difficult task since it involves not only technical knowledge, but also conceptual, social, academic and linguistic knowledge related to the course theme. At that point, we realized that active-dialogical understanding and interaction weave the IE s and the student s knowledge, who are active subjects in the productive chain of meaning, with the clear goal of promoting student's learning.